Host-directed therapies for infectious diseases: current status, recent progress, and future prospects - Zumla, Alimuddin; Rao, Martin; Wallis, Robert S; Kaufmann, Stefan H E; Rustomjee, Roxana; Mwaba, Peter; Vilaplana, Cris; Yeboah-Manu, Dorothy; Chakaya, Jeremiah; Ippolito, Giuseppe; Azhar, Esam; Hoelscher, Michael; et al. (The Lancet infectious diseases, 2016)
Despite extensive global efforts in the fight against killer infectious diseases, they still cause one in four deaths worldwide and are important causes of long-term functional disability arising from tissue damage. The continuing epidemics of tuberculosis, HIV, malaria, and influenza, and the emergence of novel zoonotic pathogens represent major clinical management challenges worldwide. Newer approaches to improving treatment outcomes are needed to reduce the high morbidity and mortality caused by infectious diseases. Recent insights into pathogen–host interactions, pathogenesis, inflammatory pathways, and the host's innate and acquired immune responses are leading to identification and development of a wide range of host-directed therapies with different mechanisms of action. Host-directed therapeutic strategies are now becoming viable adjuncts to standard antimicrobial treatment. Host-directed therapies include commonly used drugs for non-communicable diseases with good safety profiles, immunomodulatory agents, biologics (eg monoclonal antibodies), nutritional products, and cellular therapy using the patient's own immune or bone marrow mesenchymal stromal cells. We discuss clinically relevant examples of progress in identifying host-directed therapies as adjunct treatment options for bacterial, viral, and parasitic infectious diseases.